An essential role for continental rifts and lithosphere in the deep carbon cycle. Issue 12 (December 2017) - Foley, Stephen; Fischer, Tobias
Abstract The continental lithosphere is a vast store for carbon. The carbon has been added and reactivated by episodic freezing and re-melting throughout geological history. Carbon remobilization can lead to significant variations in CO2 outgassing and release in the form of magmas from the continental lithosphere over geological timescales. Here we use calculations of continental lithospheric carbon storage, enrichment and remobilization to demonstrate that the role for continental lithosphere and rifts in Earth's deep carbon budget has been severely underestimated. We estimate that cratonic lithosphere, which formed 2 to 3 billion years ago, originally contained about 0.25 Mt C km–3 . A further 14 to 28 Mt C km–3 is added over time from the convecting mantle and about 43 Mt C km–3 is added by plume activity. Re-melting focuses carbon beneath rifts, creating zones with about 150 to 240 Mt C km–3, explaining the well-known association of carbonate-rich magmatic rocks with rifts. Reactivation of these zones can release 28 to 34 Mt of carbon per year for the 40 million year lifetime of a continental rift. During past episodes of supercontinent breakup, the greater abundance of continental rifts could have led to short-term carbon release of at least 142 to 170 Mt of carbon per year, and may have contributed to the high atmospheric CO2 at several times in Earth's history. Continental rifts are stores and sources of abundant carbon, according to calculations of carbon storage, enrichments and mobilization in rift systems. Continental rift systems are likely to play an important role in Earth's deep carbon cycle.